Acupuncture Enhances Dorsal Raphe Functional Connectivity in Knee Osteoarthritis With Chronic Pain - Gao, Nan; Shi, Haiping; Hu, Sheng; Zha, Bixiang; Yuan, Aihong; Shu, Jianhua; Fan, Yinqiu; Bai, Jin; Xie, Hongyu; Cui, Jingcheng; Wang, Xiaoxiao; Li, Chuanfu; et al. (Frontiers in Neurology, 2022)
Introduction: Knee osteoarthritis (KOA) is a common disease in the elderly. Patients suffer from long-term chronic pain and reduced life quality. Acupuncture has been proved to be an effective treatment for KOA. However, the neural mechanism of acupuncture is unclear so far. Periaqueductal gray (PAG) and raphe nuclei (RPN) are essential structures associated with chronic pain in human brains. This study aims to investigate functional connectivity (FC) changes of PAG and RPN in KOA to interpret the neural mechanism of acupuncture. Methods: In 15 patients with KOA and 15 healthy controls (HC), we acquired VAS scores and resting-state fMRI images of each participant before and after acupuncture stimulation on EX-LE5 acupoint. Then, PAG and RPN were selected as seeds to perform FC analysis based on resting-state fMRI images. Finally, we compared FC patterns of PAG and RPN between KOA patients and HC and between pre-acupuncture and post-acupuncture. Correlations between FC values and VAS scores were calculated as well. Results: For PAG, FC of KOA patients was lower in the right lingual gyrus at post-acupuncture compared with HC (P < 0.001, uncorrected). For dorsal RPN, FC of KOA patients was significantly higher in right putamen at post-acupuncture compared with HC (P < 0.001, corrected with FDR), and FC changes were significant between pre-acupuncture and post-acupuncture in KOA patients. Post-acupuncture FC values between dorsal RPN and right putamen were correlated with VAS scores. For medial RPN, FC of KOA patients was lower in the right cerebellum at post-acupuncture compared with HC (P < 0.001, uncorrected), but no significant FC changes were found between pre-acupuncture and post-acupuncture in KOA patients. FC values between medial RPN and right cerebellum were not correlated with VAS scores at pre-acupuncture and post-acupuncture. Discussion: Our study demonstrated that acupuncture enhanced FC between dorsal RPN and the right putamen in KOA patients, which was associated with chronic pain intensity. This result suggests that acupuncture stimulation induces FC between dorsal RPN and striatum enhanced to drive the KOA patients’ brain to perceive the pain.